Bioimpedance analysis of body composition and rest energy expenditure in highly trained cross-country skiers - Bushmanova, E. A.; Lyudinina, A. Y. (Problems of Nutrition, 2024)
The body composition monitoring using bioimpedance analysis (BIA) is important in assessing the functional state of athletes in sports. Based on changes of body composition, it is possible to optimize the actual dietary intake, as well as successfully organize the training process.